COMPUTER-ASSISTED COLLABORATIVE WRITING AND STUDENTS’ PERCEPTIONS OF GOOGLE DOCS AND WIKIS: A REVIEW PAPER - Husam Masaoud Alwahoub; Mohd Nazri Latiff Azmi; Mohammad Halabieh (Universitas Islam Sumatera Utara (UISU), 2020)
Computer-assisted collaborative writing has been gradually employed in L2 and FL contexts due to the introduction of Web 2.0 applications and tools (i.e., Google Docs and wikis) and its benefits in developing learners’ writing skills. Accordingly, extensive literature that dealt with computer-assisted collaborative learning and learners’ perceptions towards this activity has been condensed on shelves by time passing. Thus, a review of former studies over the recent decade is called forth aiming to ameliorate the difficulties of reaching this literature and to awaken broadened knowledge in this promising area. This paper reviewed and discussed about 40 relevant articles published from 2011 to 2019 that dealt with computer-assisted collaborative writing using Web 2.0 tools, precisely Google Docs and wikis, and learners’ perceptions towards this activity (computer-assisted collaborative writing) and tools. All the articles were selected according to specific criteria, where only a true collaborative writing peer-reviewed articles were selected. After that, two main themes were synthesized: (a) collaborative writing outcomes and (b) students’ perceptions, and specific research components in relation to each theme were further reviewed and summarized using illustrative tables. Drawing on the review of this literature, the researchers discuss pedagogical implications in terms of technology integration and writing development and address future research directions including systematically reviewing this topic with teachers’ perceptions of computer-assisted collaborative writing.